A dictionary of forensic science - Bell, Suzanne (Oxford University Press, 2012)
This dictionary contains more than 1300 A-to-Z entries that cover the key concepts of forensic science, including a wide array of relevant terms from areas such as chemistry, biology, anthropology, art, engineering, firearms, trace evidence, crime scene investigation, and forensic computing. Web links to online resources are listed and regularly updated on a companion website, expanding the scope of the dictionary and pointing to more in-depth supplementary material. Many entries are complemented by case examples, figures, and photographs, which makes this paperback an ideal reference for students of forensic science, as well as professionals and those with an interest in forensics.